Succession in family businesses: Case study Luithlen Werke GmbH & Co.KG - von Plettenberg, Kira Gräfin (2019)
The present master thesis gives an overview of most relevant theoretical concepts in order to understand the unique organizational form of a family business as well as its decisive business continuity factor succession. The aim of this paper is to compare those theoretical concepts by providing insights due to a single embedded case study approach. Thereby, three family members of one particular family business are interviewed in a semi-structured way allowing an all-inclusive overview of the manifold challenges a family business face throughout its multi-generational existence. Furthermore, the research findings will show us that even with next generational successors in place the survival of a family business is not automatically guaranteed. Understanding the decisive threat of succession, it is therefore inevitable to include past succession decisions as they may lead in one or another way the future development of the three systems – family, business, and ownership.